2022
DOI: 10.4103/ijo.ijo_1379_21
|View full text |Cite
|
Sign up to set email alerts
|

Eye screening can be used to perform anemia screening and treatment in adolescent girls using ToucHb

Abstract: Purpose: Anemia is common in adolescent girls. Apprehension while drawing blood to estimate hemoglobin concentration is a barrier for confirming anemia. ToucHb, a noninvasive instrument that estimates the hemoglobin by taking an image of the exposed conjunctiva, was used during eye screening to help diagnose and treat anemia. Methods: ToucHb was used during secondary school eye screening and during house-to-house eye screening to estimate the hemoglobin concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…90 Studies have also shown that anemia detection is possible through simple observation of the eye's conjunctiva color changes. 91,92 journals.sagepub.com/home/taj…”
Section: Hypertensionmentioning
confidence: 99%
“…90 Studies have also shown that anemia detection is possible through simple observation of the eye's conjunctiva color changes. 91,92 journals.sagepub.com/home/taj…”
Section: Hypertensionmentioning
confidence: 99%